Performance of Conventional Banking, Impact of Indonesia's National Economic Recovery Program Due to the Covid 19 Pandemic - ela elliyana (Business and Entrepreneurial Review, 2022)
The goal of this study is to look at how traditional banking has performed over the previous three years, specifically the impact of LDR(X1), CAR(X2), BOPO(X3), and NIM(X4) on ROA(Y), where stimulus measures have been used to keep the economy moving forward after the COVID-19 epidemic. Research methodology: Financial services authorities provide time-series analysis of traditional banking performance reports from 2018 to 2021, processing with Stata 16 and the multiple linear regression techniques. Results: The average ROA is 2.23 percent, with a standard deviation of 0.32 percent, and swings in all independent variables may explain 80 percent of changes in bank profitability. The LDR Loan to Deposits Ratio significantly impacts bank profitability in terms of return on assets. The greater the CAR ratio, the higher the bank's profitability concerning its ROA. Assume that the BOPO grows while all other variables remain constant. In such an instance, a rise of 0.013 NIM will occur, positively impacting bank profitability on ROA. Limitations: The limitation of this research is the post-pandemic banking relaxation data. Contribution: To policymakers, to see the impact of final actions, whether they were correct or not.